An Analysis of Using Emotive Language on BBC Online World News Articles: a Semantics Study - Eka Margianti Sagimin; Cahyaning Ratri (PIKTORIAL : Journal of Humanities, 2021)
This study investigates the emotive language found on BBC online world news articles. The objectives of this study are to find out the kinds of emotive lexicon and to analyze the meaning of emotive lexicon by using semantics study. To discover the statements of the problem, this study uses the theory of Johnson-laird & Keith Oatley (1989) to identify the kinds of emotive lexicon and for the meaning of lexicon in conceptual or denotative meaning following the theory of Geoffrey Leech (1981). This study used 20 selected news articles from 4 different topics which are Business, Science and Environment, Health, and Stories on BBC World News via the website as the main data. This study used qualitative research method. Through the analysis, this study found out that there are different kinds of emotive lexicon shown in each topic through the five basic of emotional modes which are “happiness”, “sadness”, “fear”, “anger”, and “disgust”. There are 14 lexicons discovered in Business topic with 5 different kinds of the emotive lexicon, 14 lexicons in Science and Environment topic with 4 kinds of emotive lexicon, 11 lexicons shown in Health topic with 4 kinds of emotive lexicon, and 34 emotive lexicons found in Stories topic with 6 main kinds of emotive lexicon which also becomes the highest amount of the emotive lexicon written of all four topics. Moreover, the use of emotive language found in news articles can be distinctive in every topic in news, not only for the number of emotive lexicons used but also the categories of the emotion word that can help the writers in conveying the emotion or the feeling to the readers through their writings.Keywords: Emotive Language, Semantics, Denotative Meaning, News Article